2017
DOI: 10.1186/s40792-017-0318-y
|View full text |Cite
|
Sign up to set email alerts
|

Continuous transanal decompression for infants with long- and total-type Hirschsprung’s diseases as a bridge to curative surgery: a single-center experience

Abstract: BackgroundThe purpose of this study is to assess the usefulness of continuous bowel decompression using an indwelling transanal tube (ITT) for preoperative management in infants with long-segment (L)- or total (T)-type Hirschsprung’s disease (HD).Case presentationBetween 2012 and 2015, seven patients with L- or T-type HD underwent preoperative bowel management by continuous bowel decompression using an ITT during waiting period for curative surgery. Continuous bowel decompression was done using an ITT, a 10–12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In contrast to loop colostomy, a tangential-type stoma can act as a decompression and diversion window but cannot accomplish the complete division of the fecal stream. A transanal indwelling tube can manage the inflow feces and gas into the distal aganglionic bowel until definitive surgery [5–7]. Hirose et al [6] reported that transanal catheter fixation enabled decompression and prevention of enterocolitis before surgery in 2 neonates with long-segment HD, which allowed the performance of the single-stage early transanal pull-through procedure with laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to loop colostomy, a tangential-type stoma can act as a decompression and diversion window but cannot accomplish the complete division of the fecal stream. A transanal indwelling tube can manage the inflow feces and gas into the distal aganglionic bowel until definitive surgery [5–7]. Hirose et al [6] reported that transanal catheter fixation enabled decompression and prevention of enterocolitis before surgery in 2 neonates with long-segment HD, which allowed the performance of the single-stage early transanal pull-through procedure with laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…2). The method of fixation to the patient's hip was according to the technique described previously [5]. The tube was tied with a thread and was fixed by applying a tape to the hip using the thread (Fig.…”
Section: Continuous Tube Placement Treatment In the Colorectal Irrigation Technique And Its Home Managementmentioning
confidence: 99%
“…Hirose et al first reported a method of transanal catheter fixation and colonic irrigation for the preoperative management of neonates with HD [4]. Mochizuki et al also reported that this procedure was safe and effective even for long-and total-type HD [5]. This method enables intestinal decompression for a relatively long period; thus, the radical surgery can be made semielectively.…”
Section: Introductionmentioning
confidence: 99%